Komposita in den Kartwelsprachen - Henrik Holst, Jan (Georgica, 2016)
The present article discusses the concepts of semi-obscured and fully obscured compounds, as well as the theoretical views related to them. Along with consistently bringing the issue within the scope of Kartvelological research interests, ways are proposed that appear to make it possible to deepen our knowledge of individual lexical units to some extent.